Colorectal surgery 177 interventions for tumor pathology Complications at 30 days - Leites, Alejandro; Pouso, Jorge; Sarroca, Carlos (Cirugía del Uruguay, 1994)
A descriptive analysis of a series of 177 operations due to Colorrectal tumoral pathology with a high prevalence of malignant neoplasia (95.4%) is carried out. Complications rise to 30%, with 10% global mortality and 6% surgical mortality. An association between medica/ complications and mortality is found. Among surgical complications, parietal and urinary ones are frequent; there is an evident relationship between sepsis and death. T he authors make considerations lending to decrease medica/ complications which are considered avoidable, as we/1 as the surgical ones (urinary and parietal). Al/ complications need to be prevented and earfy diagnosed in order to decrease high vital and functional costs